The Efforts of Fiqh Teachers in the Habit of Dhuha Prayers at the Madrasah Ibtidaiyah Islamic Center Indramayu, Indramayu Regency - Lalan Heryanto (LECTURES: Journal of Islamic and Education Studies, 2022)
This study aims to determine the efforts of religious teachers in the habit of Duha prayer. These efforts are useful for teachers in developing the habit of worship. This research is a type of case study research. The subjects in this study were students of the Madrasah Ibtidaiyah Islamic Center Indramayu. Determination of the subject is done by snow ball sampling. Data collection techniques were carried out by interview and observation techniques. The conclusion of this study is that the results of the research show that the form of the efforts of the fiqh teacher is by 1). Providing motivation 2). Providing guidance 3). Habituation exercises and 4). Supervision. The results of the efforts of the fiqh teacher in the habit of praying Dhuha in class V students at the Madrasah Ibtidayah Islamic Center Indramayu include: 1). Making students more enthusiastic 2). Students understand more easily 3). Students are more disciplined